The role of extracellular vesicles in placental vascular complications. Issue 135 (February 2015) - Aharon, Anat
ABSTRACT: Extracellular membrane vesicles (EVs) also termed microvesicles (MVs) are secreted from different cells, are present in the blood circulation under normal physiological conditions, and their levels increase in a wide range of disease states. EVs contain proteins, growth and apoptotic factors, DNA fragments, microRNAs as well as messenger RNAs (mRNAs); therefore, they may function as regulators in cell–cell communication and mediators of cell signaling during multiple biological processes. The current review focuses on the role of EVs in healthy pregnancy and gestational vascular complications and discusses the involvement of EVs in gene regulation, placental hemostasis and cell function that overall reflect the placental–maternal crosstalk.